Digital diplomacy conversations on innovation in foreign policy - Sandre, Andreas (Rowman & Littlefield, 2015)
Through conversations with State Department officials, ambassadors, public relations executives, public policy experts, and academics, Digital Diplomacy explores what it means to be innovative in foreign policy and diplomacy